Problems encountered by volunteers assistingturkey and the surrounding earthquake area the relief efforts in Van - (:unkn) unknown (My University, 2013)
Amaç: Bu çalışmada, deprem bölgesinde görevlendirme ile veya gönüllü olarak çalışan sağlık çalışanlarının yaşadıkları sıkıntıları tespit etmek ve afetlerle ilgili deneyimlerini ve önerilerini saptamayı amaçladık. Gereç ve Yöntemler: Bu çalışma Ekim-Kasım 2011 tarihlerinde Van iline başta sağlık personeli olmak üzere yardım amacıyla gönüllü veya görevlendirme ile giden bireyler üzerinde görevi devam ederken yapılmıştır. Anket doldurmayı kabul eden personel ile yüz yüze görüşüldü ve anketin doldurulması sağlandı. Bulgular: Çalışmaya toplam 168 kişi dahil edildi ve yaş ortalamaları 31,07±8,3 (yaş aralığı 17-56) olarak hesaplandı. Katılımcıların 74ü (%44) resmi görevlendirme, 94ü (%56) ise gönüllü-görevlendirme ile gelmişlerdi. Çalışma sırasında 77 (%45,8) kişi en az bir kez sağlık problemi yaşadı. Afet bölgesinde katılımcı- ların %73,8i için görev tanımı yapılabilmiştir. Sonuç: Bölgede çalışma tanımları, ihtiyaç duyulan malzemeler, çalışma süreleri önceden belirlenip belli bir şift sistemi içinde döndürülmelidir. Bu sayede kısa sürede ve organize olarak müdahale edilmesi sağlanabileceğini düşünü- yoruz. (JAEM 2013; 12: 66-70)

Objective: In this study, we aimed to identify the difficulties encountered by the health teams and personnel working as volunteers or on assignment in the earthquake area, and to identify their experiences and recommendations regarding the disaster. Material and Methods: This study was conducted in October and Novem- ber 2011 in Van, Turkey and the surrounding region with individuals, mainly health personnel, who arrived in the city as volunteers or on assignment to assist the relief efforts. The study was conducted as these individuals carried out their duties. Face-to-face interviews were conducted with volunteers and personnel who agreed to complete the questionnaires as required. Results: A total of 168 persons were included in the study. The mean age of these individuals was calculated as 31±8 (age range 17 to 56). Of the particpants, 74 (44%) arrived in the city or the surrounding area as part of their official assignment, and 94 (56%) arrived as volunteers. During the study, 77 (46%) of the individuals experienced a health problem on at least one occa- sion. A job definition could be identified for 74% of the participants. Conclusion: The job definitions and required materials should be pre-determined and work hours rotated according to a shift system. We believe that this would allow relief efforts to be conducted more effectively. (JAEM 2013; 12: 66-70)
Van ilinde meydana gelen depremde yardıma giden gönüllülerin karşılaştığı sorunlar ve çözüm önerileri
Keywords: Acil Tıp